PENGARUH VARIASI KONSENTRASI BEAD ALGA Chlorella sp. DALAM FLAT-FOTOBIOREAKTOR UNTUK MENYISIHKAN NUTRIEN PADA PALM OIL MILL EFFLUENT (POME) - Shinta Elystia; Indah Darmayanti; Sri Rezeki Muria (Jurnal Sains dan Teknologi, 2019)
Chlorella sp. is able to utilize organic material contained in POME as a nutrition source for its growth. In this studythe removal of COD and Total Nitrogen was carried out by using POME as a cultivation medium in flatphotobioreactors. Cell immobilization is done to form beads due to Chlorella sp. has a microscopic cell, low density,and difficult to separate from the medium. To obtain the best allowance efficiency, the concentration of algal bead inthe flat-photobioreactor was varied by 6, 8, 10, 12, and 14 beads / mL of wastewater and contact times of 0, 1, 3, 5, and7 days. The results showed that the best efficiency of COD and Total Nitrogen removal was found in flatphotobioreactors with concentrations of algal bead of 12 beads/ mL of wastewater on the seventh day at 77.8% and83.5%.